PENGARUH MODEL SCAFFOLDED WRITING BERBANTUAN MEDIA GAMBAR BERKATA KUNCI PADA MINAT BELAJAR DAN KEMAMPUAN MENULIS TEKS NARASI PADA PESERTA DIDIK KELAS VII SMP NEGERI 1 BANTAENG - Ekariani; Marwiah; Ratnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the low ability to write narrative texts in class VII at SMP Negeri 1 Bantaeng. The purpose of this study is to demonstrate the impact on narrative writing skills using the scaffolded writing model assisted by picture media with key phrases and the effect on students’ learning interest after using the scaffolded writing model assisted by picture media with key phrases in seventh class students at SMP Negeri 1 Bantaeng. This research uses a quantitative approach with a quasi-experimental method. The research design is one group pretest-posttest design. The sample for this research consisted of 32 people. The instruments used in this research were tests and questionnaires. The test was used in two stages in this research, namely the pretest before being given treatment and the posttest after being given treatment. The results of the research show that the scaffolded writing model assisted by key word image media has more influence on interest in learning and the ability to write narrative texts compared to the old model used. Based on the results of the pretest and posttest with the independent sample test on SPSS, the Sig value was obtained. (2-tailed) of 0.000 is smaller than 0.05, which means that the use of the scaffolded writing model assisted by key word image media has a significant influence on students' interest in learning and the ability to write narrative texts.